Different Stages of Evolution of Prominence and the Associated CMEs - Taliashvili Enacolopas, Lela (2013)
We study the diﬀerent evolutional stages of a large quiescent prominence, mainly considering its dynamic/thermal instabilities occurred close from the boundary of coronal hole (CH). We identify the critical conditions, such as the minimum distance between the CH’s boundary and prominence channel and the emergence of a new magnetic ﬂux linked to the prominence instability and its general evolution in connection to CH. Our observations indicate peculiar ﬁlament activations prior to its thermal/dynamic instabilities, suggesting the connection of nearby CH with the general evolution of prominence and vice versa. Additionally, we analyze each evolutional stage of prominence and the associated Coronal Mass Ejections (CMEs).